2016
DOI: 10.1111/1756-185x.12952
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade and severe pericardial effusion in systemic sclerosis: report of nine patients and review of the literature

Abstract: Although cardiac tamponade or severe pericardial effusion is an infrequent complication in SSc patients, it can be the first manifestation of disease associated with the diffuse cutaneous subset. No specific treatment for this complication is known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Another cohort study evaluated the risk of recurrence and prognosis of malignant effusion following surgical repair or percutaneous intervention and found better outcomes following surgical interventions. Many studies have correlated cardiac tamponade with worse short and long‐term outcomes in the patients undergoing pericardiocentesis . Our results are in line with those observations as more patients with tamponade underwent pericardiocentesis than surgical interventions with higher mortality rates.…”
Section: Discussionsupporting
confidence: 91%
“…Another cohort study evaluated the risk of recurrence and prognosis of malignant effusion following surgical repair or percutaneous intervention and found better outcomes following surgical interventions. Many studies have correlated cardiac tamponade with worse short and long‐term outcomes in the patients undergoing pericardiocentesis . Our results are in line with those observations as more patients with tamponade underwent pericardiocentesis than surgical interventions with higher mortality rates.…”
Section: Discussionsupporting
confidence: 91%
“…Up to 25% of patients with rheumatologic diseases were unable to receive a definitive diagnosis, while others were undiagnosed for an average of 5 to 10 years. 2 The rheumatologic disorder diagnosed in this case study, scleroderma, has a prevalence of 135 million to 184 million cases in the U.S. 3 The majority of patients are female, 4 , 5 and those particularly with scleroderma present with a complication of pericardial effusion at an average age 52.2 ± 10.8 years. 1 …”
Section: Discussionmentioning
confidence: 90%
“…Steen et al in an early study reported that cardiac involvements, including congestive heart failure and pericardial effusion, preceded the onset of SRC by 6 months (13). In the study of Fernandez Morales et al, 12.5% of patients with severe pericardial effusion eventually developed SRC (10). The reasons for the association of such rare events are not completely understood yet.…”
Section: Discussionmentioning
confidence: 97%